Surface metallization resin-based material as well as preparation method and application thereof

By modifying the surface of the resin-based material with ultra-short pulse laser and electroless plating after activation treatment in the activation liquid, the problem of cumbersome and low efficiency of the surface metallization process of the resin-based material in the prior art is solved, and efficient and uniform metallization effect and excellent conductivity are achieved.

CN119843254APending Publication Date: 2025-04-18BEIJING UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510076701.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art has problems such as complicated steps, slow deposition speed, harsh deposition conditions, difficult substrate temperature control and easy oxidation of metal powder when metallization is performed.

Method used

Ultra-short pulse laser is used to modify the surface of the resin-based material. After the modified material is activated in the activation liquid, it is electroless plating to achieve surface metallization.

Benefits of technology

This method simplifies the process flow, improves the deposition efficiency, ensures good combination of metal and substrate material, improves the conductivity of the metal pattern, and avoids the fall of the metal plating layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843254A_ABST
    Figure CN119843254A_ABST
Patent Text Reader

Abstract

The invention provides a surface metallization resin-based material as well as a preparation method and application thereof. The preparation method of the surface-metallized resin-based material comprises the following steps: (1) scanning the surface of the resin-based material by adopting ultrashort pulse laser to obtain a surface-modified resin-based material, and the water contact angle of the resin-based material is 80-130 degrees; (2) activating the surface modified resin-based material in an activating solution, and cleaning to obtain an activated resin-based material; and (3) carrying out chemical plating on the activated resin-based material in a chemical plating solution. The method is convenient to operate, simple in process, high in efficiency and wide in metal layer preparation range, the prepared conductive metal pattern is uniform in thickness and good in conductivity, the bonding strength of the conductive metal pattern and a resin-based material reaches the highest 5B level, and the method can be used for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resin material processing, and in particular to a surface metallized resin-based material and a preparation method and application thereof. Background Art

[0002] Resin-based materials mainly refer to fiber-reinforced resin-based composite materials such as carbon fiber and glass fiber, which have excellent corrosion resistance, mechanical properties, thermal stability and good molding ability, and are widely used in aerospace, medical, automotive and other industries. However, due to the extremely poor surface conductivity of most resin-based materials, their application scope is greatly limited. Metallization of the surface of resin-based materials can maintain its excellent properties such as high specific strength and corrosion resistance, while giving it additional functional properties such as electrical conductivity, thermal conductivity and electromagnetic shielding, thereby greatly increasing its application scope.

[0003] At present, the technologies for metallization of resin-based material surfaces include physical vapor deposition, cold spraying, thermal spraying, etc. Patent CN110846620A uses magnetron sputtering in physical vapor deposition technology to achieve metallization of the surface of resin-based carbon fiber composite materials under vacuum, but it has problems such as cumbersome steps, slow deposition speed, and harsh deposition conditions. Patent CN115807204A uses thermal spraying technology to achieve metallization on the surface of carbon fiber composite materials. However, the obvious problem of thermal spraying is that the temperature of the substrate cannot be controlled during the deposition process, which is easy to cause certain damage to the substrate. At the same time, the metal powder is prone to oxidation during the spraying process.

[0004] Therefore, developing a simple process to achieve surface metallization of resin-based materials while ensuring good bonding between the metal and the base material so that the prepared metal pattern has excellent conductivity has very important application prospects. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a surface metallized resin-based material and a preparation method and application thereof.

[0006] In a first aspect of the present invention, the present invention provides a method for preparing a surface metallized resin-based material, the method comprising: (1) Scanning the surface of a resin-based material using an ultrashort pulse laser to obtain a surface-modified resin-based material, wherein the water contact angle of the surface of the resin-based material is 80° to 130°; (2) activating the surface-modified resin-based material in an activation solution and then washing it to obtain an activated resin-based material; (3) Chemically plating the activated resin-based material in a chemical plating solution.

[0007] According to the preparation method of the above-mentioned surface metallized resin-based material provided by the present invention, the surface of the resin-based material is modified by ultrashort pulse laser to replace the roughening and sensitization treatment of the traditional chemical plating. The modification treatment of the ultrashort pulse laser ensures the deposition effect of the noble metal ions in the subsequent activation process of the resin-based material modification, thereby realizing the metallization of the surface of the resin-based material after the chemical plating treatment. The inventor found that if the traditional continuous laser is used to modify the resin-based material, it is easy to cause significant damage to the material. Compared with the continuous laser, the ultrashort pulse laser has a small thermal accumulation effect and can accurately control the heat input, so it is an ideal light source for modifying the resin-based material. In particular, the inventor found that the water contact angle of the resin-based material with a water contact angle of 80~130° is significantly reduced after laser modification, indicating that the surface of the modified material has a large surface energy. Therefore, the resin-based material with a water contact angle of 80~130° is more likely to form a good interface with the metal coating after surface modification, avoiding the shedding of the metal coating and improving the conductivity of the material. At the same time, this method is easy to operate, simple in process, and highly efficient. It can effectively achieve modification of specific areas and then realize the subsequent deposition of different metal patterns. The prepared metal patterns have excellent conductivity, which broadens the application prospects of resin-based materials.

[0008] According to the method for preparing the surface metallized resin-based material provided by the present invention, the laser parameters of the ultrashort pulse laser include: the laser pulse width is on the order of 10 -15 ~10 -10 s, repetition rate is 20 kHz~1 GHz, laser energy density is 0.2~7 J / cm 2 , the scanning speed is 10~5000 mm / s, and the spot overlap rate is 0~85%. By controlling the laser parameters within the above range, effective modification of the surface of the resin-based material can be achieved, the subsequent precious metal deposition effect can be improved, and the bonding strength between the metal layer and the resin substrate can be increased.

[0009] According to the preparation method of the surface metallized resin-based material provided by the present invention, the surface roughness of the resin-based material is not greater than 1 μm. The surface roughness of the resin-based material is controlled to be not greater than 1 μm, so that the surface of the material after laser modification has a more suitable roughness, and it is easier to form a mechanical interlocking structure with the base material, thereby improving the interface bonding strength between the metal and the material.

[0010] It should be noted that the roughness measurement process is as follows: A laser confocal microscope is used to test the roughness of the material. The confocal microscope scans the surface of the material and records the reflected light intensity and position information of each scanning point to generate a large number of data points. These data points can be used to reconstruct the three-dimensional morphology of the sample surface. The collected data is processed by software to generate a three-dimensional morphology map of the sample surface. These morphology maps can intuitively display the microstructure and roughness characteristics of the sample surface. Finally, the surface roughness parameters of the material, such as arithmetic mean roughness (Ra), maximum height (Rz), root mean square roughness (Rq), etc., are calculated by software. These parameters can quantify the roughness of the sample surface. In this patent, Ra is used to represent the surface sample roughness in μm.

[0011] In some embodiments of the present invention, the resin-based material includes polyetheretherketone, carbon fiber reinforced polyetheretherketone composite material, polyphenylene sulfide, carbon fiber reinforced polyphenylene sulfide composite material, polyimide, carbon fiber reinforced polyimide composite material, polyetherketoneketone or carbon fiber reinforced polyetherketoneketone composite material.

[0012] According to the preparation method of the surface metallized resin-based material provided by the present invention, the water contact angle of the modified part of the surface modified resin-based material is 5 to 74°. The water contact angle of the modified part of the surface modified resin-based material is within the above range, and the material surface at the modified part has higher surface energy and chemical activity, so it is easier to form a good interface with the metal plating layer.

[0013] According to the preparation method of the surface metallized resin-based material provided by the present invention, the roughness of the modified part of the surface modified resin-based material is 3 to 10 times the roughness of the resin-based material. Compared with before modification, the surface roughness after modification is increased by 3 to 10 times, and the metal is more likely to form a mechanical interlocking structure with the base material, thereby improving the interface bonding strength between the metal and the material.

[0014] According to the preparation method of the surface metallized resin-based material provided by the present invention, the temperature of the activation treatment is 25-55°C and the time is 10-40 min. By controlling the temperature and time of the activation treatment within the above range, the deposition of precious metals is facilitated, thereby improving the metallization effect.

[0015] In some embodiments of the present invention, the activation solution includes at least one of a silver nitrate solution and a palladium chloride solution.

[0016] In some embodiments of the present invention, the concentration of the activation solution is 0.001-0.1 mol / L.

[0017] In some embodiments of the present invention, the temperature of the activation solution is 35-45° C., and the activation treatment time is 25-40 min.

[0018] According to the method for preparing a surface metallized resin-based material provided by the present invention, the temperature of the chemical plating is 20-90°C, and the time of the chemical plating is 15-60 minutes. By controlling the temperature and time of the chemical plating within the above range, metal can be effectively deposited to form a metallized pattern on the surface of the resin material.

[0019] It should be noted that chemical plating can be used to plate copper, nickel, silver, gold and their alloys on the surface of composite materials according to different solutions. For example, copper sulfate is used as the main salt, formaldehyde is used as the reducing agent, and potassium sodium tartrate is used as the complexing agent in an alkaline environment to deposit copper on the surface of the material.

[0020] In a second aspect of the present invention, a surface metallized resin-based material is provided, wherein the surface metallized resin-based material is prepared by the above method, so that the resin-based material and the metal layer of the surface metallized resin-based material have excellent bonding strength, and the metal layer has good conductivity and uniform thickness.

[0021] In a third aspect of the present invention, the present invention proposes the application of the above-mentioned surface metallized resin-based material in the aerospace field, the medical device field or the automotive industry field.

[0022] The present invention at least includes the following technical effects: The method provided by the present invention is easy to operate, simple in process and high in efficiency. It can prepare a single layer of metal element or multiple layers of different types of metals. The preparation range is wide. The prepared conductive metal pattern has uniform thickness, good conductive properties and a bonding strength with the resin-based material of up to 5B level, and can be used for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 is a scanning electron microscope image of the plane of the unmodified CF / PEEK composite material of Example 1 of the present invention; Figure 2 is a scanning electron microscope image of the plane of the modified CF / PEEK composite material of Example 1 of the present invention; Figure 3 is a scanning electron microscope image of the Cu-plated layer of the CF / PEEK material of Example 1 of the present invention; Figure 4This is a macroscopic morphology of the Cu layer conductive CF / PEEK composite material of Example 1 of the present invention; Figure 5 is a scanning electron microscope image of the Cu-plated layer of the PEEK material of Example 2 of the present invention; Figure 6 This is a macroscopic morphology of the Cu layer conductive PEEK composite material of Example 2 of the present invention. DETAILED DESCRIPTION

[0025] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0026] Example 1 The preparation process of the surface metallized resin-based material of this embodiment is as follows: (1) The selected resin-based material is CF / PEEK composite material (carbon fiber content 66%, 0° / 90° alternating weaving, 2 mm thick, produced by Jiangsu Junhua Special Plastic Co., Ltd.). CF / PEEK is placed in deionized water for ultrasonic cleaning for 10 min and then blown dry for use; (2) The CF / PEEK treated in step (1) was modified by femtosecond laser, wherein the laser wavelength was 515 nm, the pulse width was 800 fs, the pulse repetition frequency was 30 kHz, and the spot diameter was 30 μm. According to the conductive structure design, the modification of the corresponding area was achieved by changing the laser scanning path, wherein the laser scanning speed was 180 mm / s and the laser energy density was 0.614 J / cm 2 , the longitudinal overlap rate of the scanning spot is 50%, the surface roughness of the modified CF / PEEK increases from 0.49 μm of the unmodified surface to 2.97 μm, the roughness increase is close to 600%, and the water contact angle decreases from 92.39° of the unmodified surface to 31.90°; (3) placing the CF / PEEK treated in step (2) in a AgNO3 solution (AgNO3 content of 0.1 mol / L) and leaving it at 30°C for 30 min for activation; (4) The CF / PEEK treated in step (3) is placed in a copper plating solution at 40°C for 30 min, wherein the chemical copper plating solution comprises CuSO4·5H2O: 13 g / L, HCHO: 9.5 ml / L, NaOH: 14 g / L, and NaKC4H4O6·4H2O: 29 g / L. The surface is then cleaned by ultrasonic oscillation to obtain a surface copper-plated CF / PEEK, wherein the copper sheet resistance is 48.98 mΩ / sq and the bonding strength is at the 5B level.

[0027] Bonding strength test method: Use the hundred-grid knife scribing standard to measure the bonding strength level of the metal film layer and the flexible medium (GB / T9286). The specific operation method is to use the hundred-grid knife to cut 6 parallel cuts in the metal film layer, and cut another 6 parallel cuts perpendicular to the first cut, remove all loose film fragments, and use 3M tape to stick to the surface of the cut metal film layer. After about 2 to 5 minutes, peel it off at a certain angle. Observe the cut area and compare it with the six-level grading standard. If the cut edge is completely smooth and there is no shedding in the grid, it is the highest 5B grade.

[0028] The scanning electron microscope (SEM) image of the unmodified CF / PEEK composite material plane of Example 1 is as follows: Figure 1 As shown, the scanning electron microscope image of the modified CF / PEEK composite material plane of Example 1 is as follows Figure 2 As shown, from Figure 1 and Figure 2 It can be seen that the surface roughness of the modified material is significantly improved. The increase in roughness increases the specific surface area of ​​the CF / PEEK surface, providing additional mechanical locking points, thereby enhancing the physical interlocking ability of the material.

[0029] The scanning electron microscope image of the Cu-plated layer of the CF / PEEK material of Example 1 is as follows: Figure 3 As shown, from Figure 3 It can be seen that a uniform and dense copper layer is deposited on the surface of CF / PEEK, which makes the surface of the material have good conductivity.

[0030] Example 2 The preparation process of the surface metallized resin-based material of this embodiment is as follows: (1) The selected resin-based material is PEEK material (pure PEEK sheet, 2 mm thick, produced by Jiangsu Junhua Special Plastic Co., Ltd.). PEEK is placed in deionized water for ultrasonic cleaning for 10 min and then blown dry for use; (2) The PEEK treated in step (1) was modified using a femtosecond laser, wherein the laser wavelength was 515 nm, the pulse width was 800 fs, the pulse repetition frequency was 30 kHz, and the spot diameter was 30 μm. According to the conductive structure design, the modification of the corresponding area was achieved by changing the laser scanning path, wherein the laser scanning speed was 90 mm / s and the laser energy density was 0.83 J / cm 2 The longitudinal overlap rate of the scanning spot is 67%. The surface roughness of the modified PEEK increases from 0.31 μm to 1.49 μm, with a roughness increase of nearly 500%. The water contact angle decreases from 81.63° to 49.46°. (3) placing the PEEK treated in step (2) in a AgNO3 solution (AgNO3 content of 0.1 mol / L) and leaving it at 30°C for 30 min for activation; (4) Plating the PEEK treated in step (3) in a copper plating solution at 40°C for 30 min, wherein the chemical copper plating solution comprises CuSO4·5H2O: 13 g / L, HCHO: 9.5 ml / L, NaOH: 14 g / L, and NaKC4H4O6·4H2O: 29 g / L, and then cleaning the surface with ultrasonic oscillation to obtain surface copper-plated PEEK, the copper plating square resistance is 76.56 mΩ / sq, and the bonding strength reaches 5B level.

[0031] The scanning electron microscope image of the Cu-plated layer of the PEEK material of Example 2 is as follows: Figure 5 As shown, from Figure 5 It can be seen that the deposited nano copper particles are relatively uniform and dense, and can achieve the deposition of various patterned metal layers.

[0032] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a surface metallized resin-based material, characterized in that: include: (1) Scanning the surface of a resin-based material using an ultrashort pulse laser to obtain a surface-modified resin-based material, wherein the water contact angle of the surface of the resin-based material is 80° to 130°; (2) activating the surface-modified resin-based material in an activation solution and then washing it to obtain an activated resin-based material; (3) Chemically plating the activated resin-based material in a chemical plating solution.

2. The method according to claim 1, characterized in that: The laser parameters of the ultrashort pulse laser include: the laser pulse width is on the order of 10 -15 ~10 -10 s, repetition rate is 20 kHz~1 GHz, laser energy density is 0.2 ~7 J / cm 2 , the scanning speed is 10~5000 mm / s, and the spot overlap rate is 0~85%.

3. The method according to claim 1, characterized in that: The roughness of the surface of the resin-based material is no greater than 1 μm.

4. The method according to any one of claims 1 to 3, characterized in that: The resin-based material includes polyetheretherketone, carbon fiber reinforced polyetheretherketone composite material, polyphenylene sulfide, carbon fiber reinforced polyphenylene sulfide composite material, polyimide, carbon fiber reinforced polyimide composite material, polyetherketoneketone or carbon fiber reinforced polyetherketoneketone composite material.

5. The method according to any one of claims 1 to 3, characterized in that: The water contact angle of the modified part of the surface modified resin-based material is 5-74°.

6. The method according to any one of claims 1 to 3, characterized in that: The roughness of the modified part of the surface-modified resin-based material is 3 to 10 times the roughness of the resin-based material.

7. The method according to any one of claims 1 to 3, characterized in that: The activation treatment is performed at a temperature of 25-55° C. and for a time of 10-40 min.

8. The method according to any one of claims 1 to 3, characterized in that: The activation solution includes at least one of a silver nitrate solution and a palladium chloride solution; And / or, the concentration of the activation solution is 0.001-0.1 mol / L; And / or, the temperature of the activation solution is 35-45°C, and the activation treatment time is 25-40 min; And / or, the temperature of the chemical plating is 20-90° C. and the time is 15-60 min.

9. A surface metallized resin-based material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the surface metallized resin-based material according to claim 9 in the aerospace field, medical device field or automobile industry field.

Citation Information

Patent Citations

  • Surface metallization method for resin-based carbon fiber composite flexible antenna

    CN110846620A

  • Carbon fiber composite material surface metallization method and application thereof

    CN115807204A